PELATIHAN PENGGUNAAN GEMINI AI UNTUK MENINGKATKAN KOMPETENSI GURU - WIDYAH NOVIANA; Handayani, Ita; Widihastuti, Harumi (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of Community Service (PkM) is to provide counseling and training on the use of Gemini AI to improve teacher competence. One of the teacher competencies referred to in this PkM is pedagogical competence. This PkM was carried out at MI Arrahman. This activity was attended by the principal and teachers. This PkM activity was carried out for 3 days, including the introduction of artificial intelligence (AI), account creation, training in creating learning administration, learning tools, and learning evaluation. The implementation methods used include: 1) Observation stage, 2) Planning stage, 3) Preparation stage, 4) Implementation stage, 5) Discussion stage, and 6) Evaluation stage. The results of this PkM showed an increase from before the training in teacher understanding by 50% and after the training, teacher understanding increased by 100%.